Early Initiation of Breastfeeding and Exclusive Breastfeeding: A Case Study of Breastfeeding Mothers in Takalar District - Syamsuriyati; Tahir Abdullah; Burhanuddin Bahar; Andi Indahwaty; Veni Haju; Ridwan Amiruddin; Toto Sudargo; Syamsuar Manyullei (Journal of Pharmacy and Nutrition Sciences, 2019)
The coverage of exclusive breastfeeding in the Takalar District in 2011 was around 57.3% to 75.4% which means that people in Takalar District still needs exclusive nutrition and breastfeeding handling. In addition, Early initiation of breastfeeding (EIB) and exclusive breast milk from birth to the age of six months are two important breastfeeding practices in reducing infant mortality rate and increasing exclusive breastfeeding success. This study aims to look at the condition of early initiation of breastfeeding (EIB) and exclusive breastfeeding among breastfeeding mothers in Takalar District. This study was a descriptive study investigating some variables such as socio-demographics, pregnancy history, and early initiation breastfeeding practice. The population consisted of all breastfeeding mothers and samples were chosen randomly (56 subjects). Study findings indicate that the majority of the mothers had been successful in providing exclusive breast milk (92.9%). This indicates a very good situation. When viewed from the EIB implementation factor, the proportion of mothers giving birth who had practiced EIB was still low (26.8%). This indicated that there were respondents who were not successful in practicing EIB but successful in exclusive breastfeeding.